A novel thermal barrier coating for high-temperature applications. Issue 2 (1st February 2016) - Wang, Xueying; Guo, Shengnan; Zhao, Lili; Zhu, Yongping; Ai, Li
Abstract: A new thermal barrier coating system based on La1.7 Dy0.3 Zr2 O7 (LDZ), which had a lower thermal conductivity for applications above 1773 K, was prepared by the air plasma spraying (APS). The phase composition, thermal expansion coefficient, thermal conductivity, the actual heat insulation and antioxidant ablation of the as-sprayed coatings were investigated. XRD results reveal that single pyrochlore phase LDZ coating is prepared and no new phase appears after ablation at 1573 K and 1773 K. Compared to 8 wt% yttria partially stabilized zirconia (YSZ) coatings, LDZ has better phase stability, lower thermal conductivity, better actual heat insulation, antioxidant ablation and heat resistance performance. These results imply that the LDZ ceramics can be explored as candidate material for the ceramic layer in TBC system.